2010
DOI: 10.1002/jbmr.82
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction leads to high marrow adiposity and low bone mass in growing mice

Abstract: Introduction The effects of caloric restriction (CR) on the skeleton are well studied in adult rodents, and include lower cortical bone mass but higher trabecular bone volume. Much less is known about how CR affects bone mass in young, rapidly growing animals. This is an important problem because low caloric intake during skeletal acquisition in humans, as in anorexia nervosa, is associated with low bone mass, increased fracture risk, and osteoporosis in adulthood. To explore this question, we tested the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

37
320
3
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(371 citation statements)
references
References 89 publications
(92 reference statements)
37
320
3
11
Order By: Relevance
“…Alternatively, if our model for how the Achilles tendon loads calcaneal trabecular bone is correct, then our findings contradict some predictions of Wolff's "Law." Although many have found evidence for trabecular bone adaptation to changes in diet and hormones (Hodgkinson et al, 1978;Reeve et al, 1980;Devlin et al, 2010), and loading (Pontzer et al, 2006;Barak et al, 2011), others (Fajardo et al, 2007;Ryan and Walker, 2010;Shaw and Ryan, 2012;DeSilva and Devlin, 2012) have found the relationship between trabecular bone and inferred mechanical loading in primates to be more complicated. Although trabecular bone clearly is responsive to a variety of factors, Achilles tendon length may not affect trabecular properties as we had predicted.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, if our model for how the Achilles tendon loads calcaneal trabecular bone is correct, then our findings contradict some predictions of Wolff's "Law." Although many have found evidence for trabecular bone adaptation to changes in diet and hormones (Hodgkinson et al, 1978;Reeve et al, 1980;Devlin et al, 2010), and loading (Pontzer et al, 2006;Barak et al, 2011), others (Fajardo et al, 2007;Ryan and Walker, 2010;Shaw and Ryan, 2012;DeSilva and Devlin, 2012) have found the relationship between trabecular bone and inferred mechanical loading in primates to be more complicated. Although trabecular bone clearly is responsive to a variety of factors, Achilles tendon length may not affect trabecular properties as we had predicted.…”
Section: Discussionmentioning
confidence: 99%
“…Food restriction may have a harmful effect on bone growth under exercise training. A previous study reported that food restriction caused low bone strength and short bone length accompanied by a decreased bone formation and an increased bone resorption, and it decreased cortical and trabecular bone volume during rapid skeletal growth (15). Moreover, it caused abnormal levels of hormones (e.g.…”
mentioning
confidence: 99%
“…androgen) essential for skeletal acquisition (12). However, few studies have examined the influence of a combination of food restriction and exercise training on bone strength and morphology using male animals (16), although many studies have examined either the effect of food restriction on bone tissue (15,17), or the effect of mechanical loading accompanied with physical activity on bone tissue (8,18). We reported that the BMD and the bone architecture had been little affected by food restriction combined with exercise training in mature male rats (19).…”
mentioning
confidence: 99%
“…Control mice can be grouphoused, however, individual housing for all mice is ideal to control for changes in social behavior and temperature. It is also important to consider the age of the mice at the start of calorie restriction; 30% CR diet is known to have negative effects on BMD in mice when given for 9 weeks from 3-12 weeks of age (Devlin et al 2010), however, some studies suggest that calorie restriction in older mice can increase longevity (Harrison & Archer 1987) and could be protective of the skeleton in some strains.…”
Section: %mentioning
confidence: 99%